The northern raccoon (Procyon lotor) in urban environment of Kyiv and perspectives of formation of its wild populations in Ukraine - Nikolaichuk, O.; Zagorodniuk, I. (Theriologia Ukrainica, 2019)
Information on findings and status of the raccoon in the fauna of Ukraine and neighbouring countries is presented with an analysis of records in Polissia. The first case of occurrence of the raccoon in winter in a residential area of the Kyiv metropolis is described. The analysis of available sources shows the widespread practice of keeping raccoons as pets, and regular reports of raccoon escapes from captivity. Examples of records of free-living animals are given, that is, raccoons are able to survive without human concern, as well as to find food and shelter on their own. Findings in Kyiv testify the rapid synanthropization of the species, in contrast to exanthropic settlements in the neighbouring regions of Belarus, which by now disappeared. All these facts are considered as evidence for the first stages of formation of a synanthropic population of the species with the prospect of further emergence of a free-living population. Comparison of the data obtained in current surveys on alien species in Europe reveals the coincidence of such findings and the fact that they are a natural continuation of the invasion of the species in Europe with further expansion of the limits of free-living populations to the east. This is due to escapes from contact zoos and other places where the species is held in captivity, as well as the active adaptation to new living conditions due to climate warming and increased chance of survival of the species in natural conditions. The main habitats of the species under current conditions are not natural, but synanthropic locations, in particular residential areas of cities, but the prospect of exanthropization is rather possible. Considering all aspects of the broad expansion of the northern raccoon into the wild in many European countries, we conclude that currently there is a high risk of emergence of a similar situation in Ukraine. Such a scenario may have a negative impact on the local fauna unless we develop an action plan to address this issue. Наведено відомості про знахідки і статус ракуна у фауні України та суміжних країн з детальним аналізом знахідок на Поліссі, зокрема описано перший випадок виявлення виду у вільному стані в зимовий час у селітебному районі Київського мегаполісу. Аналіз доступних джерел засвідчує значне поширення практики утримання ракунів в якості домашніх тварин та регулярні повідомлення про втечі тварин з неволі. Наведено приклади виявлення цих тварин у дикому стані, тобто ракуни здатні виживати без турботи з боку людини, а також знаходити їжу та сховища самостійно. Київські знахідки засвідчують швидку синантропізацію виду, на відміну від екзантропних поселень суміжних регіонів Білорусі, які на даний момент часу припинили існування. Все це розглядається як свідчення перших етапів формування синантропної популяції виду з перспективою подальшого формування вільної популяції. Порівняння отриманих даних з сучасними оглядами щодо чужорідних видів тварин в Європі показує невипадковість таких знахідок і те, що вони є закономірним продовженням розвитку інвазії виду в Європі з подальшою експансією меж поширення вільних популяцій на схід. Все це відбувається за рахунок втеч з контактних зоопарків та інших місць, де вид утримується в неволі, а також активного пристосування до нових умов існування у зв'язку з потеплінням клімату і збільшення імовірності виживаності виду в природних умовах. Основним середовищем існування виду за сучасних актуальних умов є не природні, а синантропні місцезнаходження, зокрема селітебні зони міст, але перспектива екзантропізації є доволі реальною. Беручи до уваги всі аспекти широкої експансії ракуна північного в дику природу в багатьох європейських країнах, ми маємо зробити висновок, що нині в Україні є високий ризик повторення такого сценарію. Він може мати сильний негативний вплив на місцеву фауну, якщо ми не підготуємо концепцію вирішення цієї проблеми.